The relationship of the application of guided imagery therapy techniques towards pain intensity of maternal post caesarian section operation in postnatal care at the maternity hospital in the city of Padang - Indriani, Silfina; Darma, Ika Yulia; Ifayanti, Titin; Restipa, Ledya (International Journal Of Community Medicine And Public Health, 2021)
Background: Most of the maternity mothers experience discomfort disorders due to the pain felt by the mother after caesarean section surgery. The pain causes disruption of the mother’s activities after giving birth, the mother has difficulty breastfeeding her baby, and has difficulty doing physical activities. The pain results from surgical wounds on the abdominal wall and uterine wall of the mother. The pain experienced by each mother is different, ranging from low pain levels to severe pain levels. Methods: This type of comparative analytic research with a cross sectional study approach with one group pretest and posttest design. As many as 30 samples of post caesarean section delivery mothers were taken by purposive sampling technique. Marginal homogeneity test was used for research analysis. Results: The study showed that there was a decrease in the level of post-partum labor pain before and after the intervention of guided imagery therapy. Before the intervention, most of the respondents (46.7%) had moderate pain levels (4-6), after giving the intervention some respondents (43.3%) had mild pain levels. Statistical test showed a significant relationship with a significance value of 0.000 (p value <0.05). Conclusions: Giving guided imagery therapy to post caesarean section delivery mothers is able to reduce the level of pain that the mother experiences without causing additional risk for the mother. This therapy provides a sense of comfort and relaxation for the mother through the imagination generated by the mother in her mind so that it diverts and reduces the pain that the mother is experiencing.